2001
DOI: 10.1037/0097-7403.27.3.219
|View full text |Cite
|
Sign up to set email alerts
|

Shock-induced hyperalgesia: IV. Generality.

Abstract: Brief-moderate shock (3, 0.75 s, 1.0 mA) has opposite effects on different measures of pain, inducing antinociception on the tail-flick test while lowering vocalization thresholds to shock and heat (hyperalgesia) and enhancing fear conditioned by a gridshock unconditioned stimulus (US). This study examined the generality of shock-induced hyperalgesia under a range of conditions and explored parallels to sensitized startle. Reduced vocalization thresholds to shock and antinociception emerged at a similar shock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
38
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 65 publications
(277 reference statements)
6
38
2
Order By: Relevance
“…The present results shed light on the mechanisms that underlie findings of shock-induced sensitization of pain reactivity, startle, and learning reported in previous studies (Boulis and Davis 1989;Davis 1989;Illich et al 1995;King et al 1996;Crown et al 2000;Meagher et al 2001). One possible mechanism was that exposure to an aversive event has an effect that is limited to stimuli with the same valence.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…The present results shed light on the mechanisms that underlie findings of shock-induced sensitization of pain reactivity, startle, and learning reported in previous studies (Boulis and Davis 1989;Davis 1989;Illich et al 1995;King et al 1996;Crown et al 2000;Meagher et al 2001). One possible mechanism was that exposure to an aversive event has an effect that is limited to stimuli with the same valence.…”
Section: Discussionsupporting
confidence: 72%
“…However it is possible that unconditioned fear or anxiety mediates the effects of moderate shock. Although we (Meagher et al 2001) and others (Davis 1989) have reported that shock enhances startle in a new context, a finding indicative of a general sensitization of stimulus processing, this does not necessarily implicate anxiety. Indeed, none of the common unconditioned fear/ anxiety tests examined (freezing, elevated plus maze, shock-probe burying, the social interaction test) has yielded evidence of anxiety-like behavior (Sieve et al 1999;Ferguson et al unpublished observations).…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations